(untitled) (Revista Brasileira Multidisciplinar, 2013)
The study evaluated the self-perception of oral health in institutionalized and non-institutionalized elderly in the city of Araraquara -SP. The selected participants were 40 residents at a long stay institution (LSI) and 40 regulars from a group of seniors (SESI), aged between 60 and 95 years, of both genders. Participants were asked about their socio- demographic conditions, they performed a cognitive assessment test based on the Mini Mental State Examination (MMSE) and subsequently were evaluated for the self-perception of oral health with GOHAI (Geriatric Oral Health Assessment Index). The data were analyzed descriptively. The results showed that prevailed females, aged between 70 and 79 years, mostly illiterate or with incomplete primary education,50.0% living with a partner and 25.0% alone or with family. Both groups, the non- institutionalized and institutionalized ones, were considered normal in cognitive assessment (87.5% and 65.0% respectively). For GOHAI, 85.0% in SESI and 92.5% in LSI felt no discomfort when swallowing food. Regarding satisfaction with teeth and dentures, 72.5% of the group of LSI were considered as partly happy or unhappy. In clinical evaluation there was was frequent complaint of dry mouth, 85.0% of SESI prosthesis users, of which 62.5% were satisfactory; in the SLI, 72.5% wore dentures, of which 22.5% presented excessive wear. Thus, we can conclude that the self-perception of oral health of institutionalized and non-institutionalized elderly is low, which suggests the planning of education and prevention actions in oral health of major diseases that affect these individuals.